Effect of a 16-week Bikram yoga program on heart rate variability and associated cardiovascular disease risk factors in stressed and sedentary adults: A randomized controlled trial - Zoe L. Hewett; Kate L. Pumpa; Caroline A. Smith; Paul P. Fahey; Birinder S. Cheema (BMC, 2017)
Abstract Background Chronic activation of the stress-response can contribute to cardiovascular disease risk, particularly in sedentary individuals. This study investigated the effect of a Bikram yoga intervention on the high frequency power component of heart rate variability (HRV) and associated cardiovascular disease (CVD) risk factors (i.e. additional domains of HRV, hemodynamic, hematologic, anthropometric and body composition outcome measures) in stressed and sedentary adults. Methods Eligible adults were randomized to an experimental group (n = 29) or a no treatment control group (n = 34). Experimental group participants were instructed to attend three to five supervised Bikram yoga classes per week for 16 weeks at local studios. Outcome measures were assessed at baseline (week 0) and completion (week 17). Results Sixty-three adults (37.2 ± 10.8 years, 79% women) were included in the intention-to-treat analysis. The experimental group attended 27 ± 18 classes. Analyses of covariance revealed no significant change in the high-frequency component of HRV (p = 0.912, partial η 2 = 0.000) or in any secondary outcome measure between groups over time. However, regression analyses revealed that higher attendance in the experimental group was associated with significant reductions in diastolic blood pressure (p = 0.039; partial η 2 = 0.154), body fat percentage (p = 0.001, partial η 2 = 0.379), fat mass (p = 0.003, partial η 2 = 0.294) and body mass index (p = 0.05, partial η 2 = 0.139). Conclusions A 16-week Bikram yoga program did not increase the high frequency power component of HRV or any other CVD risk factors investigated. As revealed by post hoc analyses, low adherence likely contributed to the null effects. Future studies are required to address barriers to adherence to better elucidate the dose-response effects of Bikram yoga practice as a medium to lower stress-related CVD risk. Trial registration Retrospectively registered with Australia New Zealand Clinical Trials Registry ACTRN12616000867493 . Registered 04 July 2016.